Literature Study on Problems of Office Management Vocational School Teachers in Implementing Learning Technology - Basuki, Andi; Susilowati, Eni; Umatin, Choiru (PT. BATARI EDU CALYA, 2024)
This systematic literature review investigates the challenges faced by vocational school teachers in implementing educational technology. Adopting the PICOC framework, it synthesizes findings from 10 articles published between 2014-2024, selected from Scopus, Web of Science, EBSCOhost, and ProQuest databases. The review explores factors influencing teachers' readiness and effectiveness in integrating technology, such as digital competence, infrastructure, and leadership support. Key challenges identified include time constraints, inadequate training, and limited technical support. Strategies to enhance readiness involve continuous professional development, ICT expert support, diverse training programs, and collaborative learning communities. The findings contribute to developing effective policies and initiatives to support vocational teachers in successfully leveraging technology, ultimately improving education quality and preparing students for the digital era.